1979
DOI: 10.1136/thx.34.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary gas exchange during exercise in young asthmatic patients.

Abstract: Pulmonary function was examined in 19 young asthmatic patients at rest and during two levels of exercise. Findings at rest included decreased flow rates, increased residual volume, normal minute (VE) and alveolar (VA) ventilation, increased ratio of physiological dead space to tidal volume (VD/VT), increased alveolar-arterial oxygen tension difference (A-a Po2), and mild arterial hypoxaemia and desaturation. On exercise there was a normal increase in VE and VA, the VD/VT and the A-a Po2 decreased towards norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
3
8
1
Order By: Relevance
“…This further confirms that the ventilationlperfusion inequality was the cause of the decreased Pa02. The acidosis we found in this study during exercise has been reported to occur in asthmatic children and adults also by others (21,23,24) and has been attributed to an increase in arterial blood lactate (23).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This further confirms that the ventilationlperfusion inequality was the cause of the decreased Pa02. The acidosis we found in this study during exercise has been reported to occur in asthmatic children and adults also by others (21,23,24) and has been attributed to an increase in arterial blood lactate (23).…”
Section: Discussionsupporting
confidence: 87%
“…In group 2 dead space ventilation was somewhat higher and the ventilation-perfusion inequality measured by P(A-a)02 more marked. In previous studies of gas exchange during exercise in asthmatic children, unchanged or improved blood gas values have been reported in children with normal blood gas values or mild hypoxemia at rest before exercise (20,21,22). In this study we observed a slight but significant fall in PaO, most marked in the children with severe asthma.…”
Section: Discussionsupporting
confidence: 66%
“…A number of studies of adults have found both comparable and reduced physical fitness in asthmatics with respect to healthy controls [2,3,[22][23][24], and the relative importance both of disease severity and hypoactivity has continued to be debated. In the paediatric age group, most studies during the last 30 yrs have found that asthmatic children have lower work/aerobic capacity than healthy controls [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies on exercise performance in asthmatic patients, there are still contradictory data concerning the presence of a limited physical fitness in this population. Impairment of physical performance in asthma has been reported by a number of studies, whilst others have found that work capacity is not reduced [2][3][4][5]. Concerns are also raised about exercise capacity and safety in asthmatic children, and particular caution is sometimes advocated for those who wish to attend physical activities or competitive sports [6][7][8][9][10].…”
mentioning
confidence: 99%
“…Studies on the dynamic re sponses of ventilation and gas exchange during exercise have shown normal or reduced values for aerobic power and working capacity in asthmatic children [4][5][6].…”
Section: Introductionmentioning
confidence: 99%